Media Framing Strategy by Public Relations Consultants for Ultra Micro Holding - Saptono Ariyanto; Kussusanti Kussusanti (Universitas Multimedia Nusantara, 2026)
This study examines the media framing strategies employed by public relations consultants during the formation of Indonesia’s Ultra Micro State-Owned Enterprises (SOEs) Holding. Focusing on IGICO Public Affairs Advisory, the consultancy engaged by PT Bank Rakyat Indonesia (Persero) Tbk, PT Pegadaian, and PT Permodalan Nasional Madani (PNM), the study adopts a constructivist paradigm and a qualitative case study approach. Data were obtained through in-depth interviews with three consultants and document analysis, and analyzed using the Miles, Huberman, and Saldaña interactive model. Drawing on Goffman’s framing theory and the 7C’s Model, the findings indicate that media framing originated from a pre-framing stage involving audience research, issue mapping, risk identification, and narrative design. The strategy was implemented through seven interrelated communication elements and operated within a competitive communication arena characterized by competing narratives surrounding the holding. Based on these findings, the study proposes the Strategic Narrative Construction Model in Organizational Transformation, consisting of organizational issues, pre-framing, narrative construction, competitive communication arena, integrated 7C’s execution, and relational and reputational outcomes. The model highlights strategic narrative construction as a key mechanism for building public legitimacy during large-scale organizational transformation.